A practical method of drug provocation testing to prove tolerance to alternative drugs in drug hypersensitivity - DAMADOĞLU, Ebru (Turk J Med Sci, 2021)
BACKGROUND/AIM: Drug provocation tests (DPTs) are the gold standard method performed at the end of a stepwise approach in a drug allergy workup. Drug provocation tests are administered as a single drug on a test day. Testing more than one drug in a day is a feasible option and could be a safe and time- and manpower-saving procedure in well-selected patients. The aim of the present study was to investigate the efficacy and safety of performing a DPT with two or three alternative drugs in one test day (Hacettepe method). MATERIALS AND METHODS: Adult patients who were admitted with drug hypersensitivity between August 2010 and December 2016 and underwent DPTs with the described method were included. The method was based on performing DPTs with two or three different, alternative drugs on the same test day. Data was obtained from standard drug provocation test forms and from patient files. RESULTS: A total of 1448 DPTs were performed by the Hacettepe method in 1131 patients. The reaction rate was 5.45% (n = 79), and none of the reactions were severe. The Hacettepe method saved 19.95 DPTs per month which was a considerable time savings. CONCLUSION: In cases of proven drug hypersensitivity reactions, performing a drug provocation test with a combination of two or three different, alternative drugs instead of one saved time and manpower and was a safe procedure. We recommend implementing this method in drug allergy workups.